Use of Human Induced Pluripotent Stem Cell–Derived Cardiomyocytes in Preclinical Cancer Drug Cardiotoxicity Testing: A Scientific Statement From the American Heart Association. Issue 10 (25th October 2019) - Gintant, Gary; Burridge, Paul; Gepstein, Lior; Harding, Sian; Herron, Todd; Hong, Charles; Jalife, José; Wu, Joseph C.
Abstract : It is now well recognized that many lifesaving oncology drugs may adversely affect the heart and cardiovascular system, including causing irreversible cardiac injury that can result in reduced quality of life. These effects, which may manifest in the short term or long term, are mechanistically not well understood. Research is hampered by the reliance on whole-animal models of cardiotoxicity that may fail to reflect the fundamental biology or cardiotoxic responses of the human myocardium. The emergence of human induced pluripotent stem cell–derived cardiomyocytes as an in vitro research tool holds great promise for understanding drug-induced cardiotoxicity of oncological drugs that may manifest as contractile and electrophysiological dysfunction, as well as structural abnormalities, making it possible to deliver novel drugs free from cardiac liabilities and guide personalized therapy. This article briefly reviews the challenges of cardio-oncology, the strengths and limitations of using human induced pluripotent stem cell–derived cardiomyocytes to represent clinical findings in the nonclinical research space, and future directions for their further use.